Current status of 1,4-Naphthoquinones and their derivatives for wound healing - Pooja Kumari; Vikramjeet Singh; Vinay Kant; Munish Ahuja (Elsevier, 2024)
Cutaneous wounds are a major healthcare concern affecting millions of people as they fail to heal properly and can result in life threatening conditions and high economic loss. Wound healing is a complex, multifaceted process involving four consequent stages: haemostasis, inflammation, proliferation, and tissue remodelling. These phases work in coordination to restore the integrity of damaged skin and underlying tissues. 1,4-Naphthoquinone compounds and their derivatives have emerged as promising candidates in wound management. Herein, natural compounds such as lawsone, juglone, shikonin, plumbagin along with their derivatives have been discussed for wound healing potential with special emphasis on structural activity relationships. This review provides a comprehensive discussion on the chemical reactivity, biological activities, and mechanisms of action of these naphthoquinone-based compounds, particularly their antibacterial properties, which play a crucial role in wound healing. The review highlights the importance of elucidating structure-activity relationships to overcome challenges associated with poor solubility, low antibacterial efficacy, and the presence of inevitable impurities in plant extracts. Additionally, the review emphasizes the significance of developing diverse naphthoquinone derivatives at the laboratory scale to expand the repertoire of potential wound healing agents.